The Malays: A Retrospective Examination On Identity Through Selected Writings By Munshi Abdullah, Za'ba, Syed Hussein Alatas And Mahathir Mohamad - Norhaili Massari; Mohd Muzhafar Idrus; Fariza Puteh-Behak; Normazla Ahmad Mahir (Academic Inspired Network, 2024)
Societies are often fraught with cracks, displacement, and conflicts that are almost always intersected with local and global junctures. These issues, be it seemingly chaotic or minute, need to be noticed and addressed in some ways or another pertinent to the development and survival of the society. Issues which are not tackled early, in time, would have the propensities of multiplying or becoming more acute, and slowly engulf, and may even jeopardize a society. Munshi Abdullah, Za’ba, Syed Hussein Alatas and Mahathir Mohamad are important Malay personages in Malaysia who have written important texts relating to Malays’ identity, history and socio-political milleu in their own respective roles, as writers, educationist, sociologist and political leader. They are undeniably the Malay intellects who are able to present objective analyses of the Malays of their own time, presided with advanced knowledge, observation and experience. This paper examines their selected writings, that echo their thoughts and writings that they share about the Malays which are crucial cornerstones to attempts at providing a holistic view in the discussion and understanding about the identity of the Malays by looking into their past, which would be insightful to their survival of the present and the future. By combining these three literary writings, interpretative approaches to understanding cultural crises can be established.